2011
DOI: 10.1097/prs.0b013e318200afdb
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Interethnic Variability in Facial Dimensions

Abstract: Background The earliest recorded facial proportional analysis is in the Greek neoclassical canons (c. 450 B.C.). In contemporary times, there has not yet been a study that describes the relative differences in facial proportions among the world’s different ethnic groups. The specific aim of this project is to perform a systematic review of data from the existing literature in order to evaluate the degree of variability in the facial dimensions among various ethnic groups. Methods A PubMed database review ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 33 publications
5
66
0
Order By: Relevance
“…Subjects were selected if their Likert score was B 2 (i.e., exclusively or near exclusively homosexual) and they self-identified as ''homosexual/gay/ lesbian''or if their Likert score was C 6 (i.e., exclusively or near exclusively heterosexual) and they self-identified as ''heterosexual/straight. ''Only White subjects were included to remove variation in facial structure attributable to ethnicity (Fang, Clapham, & Chung, 2011). Some were excluded because they were not posed in neutral expressions, were not facing the camera directly, or the face was obscured.…”
Section: Subjectsmentioning
confidence: 99%
“…Subjects were selected if their Likert score was B 2 (i.e., exclusively or near exclusively homosexual) and they self-identified as ''homosexual/gay/ lesbian''or if their Likert score was C 6 (i.e., exclusively or near exclusively heterosexual) and they self-identified as ''heterosexual/straight. ''Only White subjects were included to remove variation in facial structure attributable to ethnicity (Fang, Clapham, & Chung, 2011). Some were excluded because they were not posed in neutral expressions, were not facing the camera directly, or the face was obscured.…”
Section: Subjectsmentioning
confidence: 99%
“…However, the researchers 415 included studies conducted on both faces and skulls, and did not discuss the possibility of 416 differences between ethnicities. Previous evidence has shown that facial dimensions vary 417 across ethnicities (Fang et al, 2011). I therefore reanalysed their data while taking into 418 account the possibility of differences between faces and skulls, and the potential effect of 419 ethnicity.…”
Section: Reanalysis Of Geniole Et Al (2015) 412 413mentioning
confidence: 99%
“…The average height of an adult human face is approximately 18cm (Fang, Clapham, & Chung, 2011). At what Hall (1966) calls the "close phase of personal distance" Foveated vs Non-Foveated Facial Features 4 (~76-45cm), a face will thus subtend visual angles of 13.4-22°, at far personal distances (~122-76cm), 8.4-13.4°, and at close social distances (~213-122cm), 4.8-8.4°.…”
Section: Foveal Vs Extrafoveal Vision and Its Relevance For Face Permentioning
confidence: 99%